2021
DOI: 10.1007/s00726-021-02968-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen metabolism as a regulator of proline dehydrogenase/proline oxidase-dependent apoptosis/autophagy

Abstract: Recent studies on the regulatory role of amino acids in cell metabolism have focused on the functional significance of proline degradation. The process is catalysed by proline dehydrogenase/proline oxidase (PRODH/POX), a mitochondrial flavin-dependent enzyme converting proline into ∆1-pyrroline-5-carboxylate (P5C). During this process, electrons are transferred to electron transport chain producing ATP for survival or they directly reduce oxygen, producing reactive oxygen species (ROS) inducing apoptosis/autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…We found that, in MCF-7 shPRODH/POX clones, the generation of NAD+/NADH and NADP+/NADPH was decreased in comparison to MCF-7 cells carrying PRODH/POX. NADP+ and NADPH are necessary when P5C is reduced to proline [ 29 ]. The reduction in NAD+/NADH and NADP+/NADPH levels reduces the availability of nucleotides for DNA biosynthesis and, as result, cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in MCF-7 shPRODH/POX clones, the generation of NAD+/NADH and NADP+/NADPH was decreased in comparison to MCF-7 cells carrying PRODH/POX. NADP+ and NADPH are necessary when P5C is reduced to proline [ 29 ]. The reduction in NAD+/NADH and NADP+/NADPH levels reduces the availability of nucleotides for DNA biosynthesis and, as result, cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous teams have demonstrated that proline is involved in many biochemical processes playing a significant role as an osmoprotectant, metal chelator, protein chaperone, ROS scavenger, energy source, a regulator of redox balance and NADP+/NADPH level in the cytosol, as well as a signaling molecule in apoptosis/autophagy [ 127 ]. Proline metabolism has also been implicated as a metabolic pathway impacted on DNA biosynthesis and epigenetic modifications [ 129 ]. Proline synthesis, degradation, and cycling are dysregulated in the microenvironment of cancer cells leading to the impairment of cell proliferation, survival, metastasis, and extracellular matrix function.…”
Section: Role Of Proline Metabolism In Gynecological Cancersmentioning
confidence: 99%
“…P5C dehydrogenase (P5CDH) using nicotinamide adenine dinucleotide converts GSA to glutamate that can enter the TCA cycle as an α-ketoglutarate. Proline is also converted by OAT into ornithine, a component of the urea cycle [ 129 ]. Moreover, proline can be incorporated into collagen molecule, which is a reservoir for proline, since approximately 25% of all its residues constitute prolyl or hydroxyprolyl groups [ 132 ].…”
Section: Role Of Proline Metabolism In Gynecological Cancersmentioning
confidence: 99%
See 2 more Smart Citations